Investigating Risk Factors for Low-Birth-Weight Infants Born to Mothers Referring to Community Health Centers in the City of Yazd - Ali Dehghani; Marzieh Sobhani; Mahmoud Nouri Shadkam; Hossein Falahzadeh; Masoud Mohammadi; Aboalfazl Sharifi (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: One of the most valuable indicators determining the health status of a community is the birth weight of infants. Thus, the purpose of this study was to investigate risk factors affecting low-birth-weight infants born to mothers visiting community health centers in the city of Yazd in Iran. Methods: The present study was a retrospective cohort research on 280 mothers visiting to community health centers in two groups of mothers with infants weighing less than 2500 grams (case) and those with babies weighing more than 2500 grams (control). The data were also collected by interviewing mothers and reviewing the information inserted in their health records. Such data were then entered into the SPSS software (Version 19) and analyzed through Chi-square test, independent t-test, as well as logistic regression analysis. Results: The mean and the standard deviation of birth weight in the case group were 2171.4 ± 339.85 grams and they were equal to 3222.5±390.78 grams in the control group. Besides, the results of the analysis revealed that maternal education (P= 0.05), type of delivery (P= 0.02), birth order (P= 0.02), maternal occupation (P= 0.03), pregnancy-induced hypertension (P= 0.008), and gestational age (P= 0.000) were correlated with low-birth-weight infants. Conclusion: Considering that low birth weight was related to factors that could be controllable in most circumstances, measures such as training mothers, promoting quality of prenatal care, and planning for childbearing among mothers are recommended.